Covalently Linked Organic Networks - Addicoat, Matthew A.; Tsotsalas, Manuel (Frontiers in Materials, 2015)
In this review, we intend to give an overview of the synthesis of well-defined covalently-bound organic network materials such as covalent organic frameworks (COFs), conjugated microporous frameworks (CMPs) and other “ideal polymer networks” and discuss the different approaches in their synthesis and their potential applications. In addition we will describe the common computational approaches and highlight recent achievements in the computational study of their structure and properties. For further information the interested reader is referred to several excellent and more detailed reviews dealing with the synthesis [Dawson 2012; Ding 2013; Feng 2012] and computational aspects [Han 2009; Colón 2014] of the materials presented here.